PENGARUH PROMOSI, KUALITAS PELAYANAN, DAN CITRA BANK TERHADAP KEPUASAN NASABAH (Studi Pada Bank Muamalat Cabang Kediri) - Mellania Nur S; Edwin Agus B; Rafikhein Novia Ayuanti (Musytari : Neraca Manajemen, Akuntansi, dan Ekonomi, 2023)
This research aims to determine the influence of promotion, service quality and bank image on customer satisfaction. The research method used is a quantitative method with a descriptive approach. Data collection in this research was carried out by distributing questionnaires to customers of Bank Muamalat Kediri Branch and calculated using the SPSS Version 25 application. Data analysis techniques used included Validity Test, Reliability Test, Classical Assumption Test, Multiple Linear Regression Analysis, T Test, F Test , and Test of the Coefficient of Determination R2. In the validity test, it is known that all statement items on the variables (X1, X2, X3 and Y) have a significance value of 0.000 < 0.05, so that each variable is declared valid. Then in the reliability test it was discovered that each variable had a Cronbach's Alpha value > 0.60, so the variable was declared reliable. Furthermore, in the t test it is known that all variables (promotion, service quality and bank image) have positive values ​​and the significance is <0.05 so that it is stated that they partially have a significant effect on customer satisfaction. Then in the F test it is known that the Sig value. for all variables together it is 0.000 < 0.05 and the value of Fcount > Ftable is 0.7,597 > 2.49, it can be concluded that the variables promotion, service quality and bank image simultaneously affect customer satisfaction at Bank Mamalat Kediri Branch .